Studi Implementasi Pendekatan Contextual Teaching and Learning pada Mata Pelajaran Fiqih di Madrasah Aliyah - Lidiya Puningsi (Reflection : Islamic Education Journal, 2024)
The essence of education as stated in the Preamble to the 1945 Constitution is to educate the nation, namely to form citizens who are creative and innovative in applying knowledge to face challenges in social, national, and state life. This study aims to determine the form of learning innovation applied by teachers in the Fiqh subject, especially in the material on usury at Madrasah Aliyah An Nur Pagar Jati. The method used is qualitative research with a field study approach. Data collection was carried out through interviews with subject teachers and students of class XI IPS 1 who were the subjects of the application of learning strategies. The strategy applied is the Contextual Teaching and Learning (CTL) approach. Based on the results of the study, the CTL strategy has been implemented well at MA An Nur Pagar Jati and is able to improve students' understanding of the teaching material. To support the continuous improvement of the quality of education, evaluation and development of learning strategies need to be carried out continuously.